Analisis Efektivitas Biaya Kombinasi Risperidone-Clozapine Dengan Risperidone-Olanzapine Pada Pasien Skizofrenia - Tiara Sani Ardiana; Delina Hasan; Ahmad Fuad Afdhal; Lahargo Kembaren (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2021)
Abstract Schizophrenia is a severe mental disorder characterized by significant distortions in thoughts and perceptions, accompanied by inappropriate emotions Antipsychotics are the mainstay of schizophrenia and require a long healing time and require high adherence to treatment. Most alternative antipsychotic therapies require pharmacoeconomic studies, particularly Cost Effectiveness Analysis which is useful in balancing patients’ expenditure by determining alternative treatments. The purpose of this study was to determine the effectiveness, eficiency and unit cost of the antipsychotic drug combination risperidone-clozapine dan risperidone-olanzapine. This research method used cross-sectional, analytical descriptive design and data collection is carried out prospectively from the medical record of schizophrenics, while detailed data on treatment costs are obtained from the financial section of inpatients at the hospital Dr. H. Marzoeki Mahdi Bogor from May to July 2019. The results of the study showed that the effectiveness of the largest antipsychotic combination therapy to increase the value of GAF was the combination of risperidone-olanzapine by 36 patients with an average difference in Initial GAF and Final GAF of 14.11, while the combination of risperidone-clozapine ie as many as 35 patients with an average difference in value Initial and Final GAF of 10.06. While the cost effectiveness based on the increase in final GAF value in the combination of risperidone-clozapine antipsychotic and risperidone-olanzapine antipsychotic combination in sequence is IDR.6,312,800. and IDR. 5,628,684. This value can be obtained from the calculation of the unit cost, the calculation of costs incurred in real where the cost is calculated for the service unit. It can be concluded that the risperidone-olanzapine antipsychotic combination is more cost effective than the risperidone-clozapine antipsychotic combination. Keywords: antipsychotics, effective and efficient, risperidone-clozapine combination, risperidone-olanzapine combination, schizophrenia.